Decreasing the residential energy consumption in the Portuguese residential sector: potential of energy saving behaviours - Sabino, C. (2015)
Buildings are part of a city, being the residential buildings responsible for a considerable share of the energy consumption. The energy consumption associated with the different residential energy services (lighting, cooking, water heating, etc.) is influenced by the way consumers use each of them. Accordingly, consumers play an important role on the residential energy consumption and up to 20% energy savings can be achieved by actions targeting behaviour. This work focuses on the Portuguese case, and analyses the adoption rate of a set of energy saving behaviours associated with a group of residential equipment: lighting systems, washing machine, refrigerator, television, computer and dishwasher. The most common consumers’ behaviour were identified for each equipment, and Portuguese studies which quantitatively evaluated the adoption rates of those behaviours were reviewed. A comparison is performed concerning the different values of adoption rates obtained from different studies. The different scopes and methodologies employed by the different studies make the comparison a challenging task. Behaviours, which the adoption rate did not address in previous studies conducted in the country, are identified, such as the case of using daylight, instead of artificial light, during the day.